IMPLEMENTASI METODE WIRELESS DISTRIBUTION SYSTEM DALAM PERANCANGAN JARINGAN HOTSPOT SERVER PADA PT INDOTAMA NIAGA HOKKI - Supianto, Supianto; Sitohang, Sunarsan (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2023)
PT Indotama Niaga Hokki is a private company so it is not related to the government which is located in the city of Batam, Riau Islands, internet network facilities at PT Indotama Hokki use ISP from PT Telkom, still using ethernet connected to a switch to connect to the internet. With the increasing use of laptops and mobile phones at PT Indotama Hokki, it is necessary to update the existing network.The Wireless Distribution System method is a technical method of connecting one Access Point to another using wireless media in a Local Area Network. With WDS we can develop wireless networks without using cables. With WDS, WLAN workspaces can be expanded without connecting the Access Point with a wired backbone system.The results of this study indicate that wireless network users at PT Indotama Hokki where the application of wireless networks using the Wireless Distribution method aims to expand the wireless network at PT Indotama Niaga Hokki, so that by using the Wireless Distribution System as a repeater to make it easier for users to access the internet with different rooms. or building without having to log in again to be able to access the internet.